Canine third eyelid hemangioma - A case report - de Aguiar, Mari Alba Trojan; Junior, Domingos de Faria; de Castro, Bruno Gomes (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Aguiar M.A.T., Faria Junior D & Castro B.G. [Canine third eyelid hemangioma - A case report.] Hemangioma em terceira pálpebra de cão - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(1):30-32, 2016. Semiologia Animal, Universidade Federal de Mato Grosso, Campus Universitário de Sinop, Av. Alexandre Ferronato, 1200, Setor Industrial, Sinop, MT 78557-267, Brasil. E-mail: castrobg@ufmt.br Ocular neoplasms cause discomfort, loss of vision or may also reflect systemic diseases. This study aimed to report a case of canine third eyelid neoplasia. After the surgical procedure, tissue was sent for a Pathology Laboratory where the neoplasic mass was described as a hemangioma. In the post-surgical period, the animal was re-evaluated and no recurrence was verified.